1997
DOI: 10.1002/(sici)1096-8628(19970627)70:4<421::aid-ajmg17>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of malformations in the axial skeleton in human trisomy 13 fetuses

Abstract: The purpose of this study was to analyse the development of the axial skeleton in human trisomy 13 fetuses and to define which fields in the axial skeleton are affected in this condition. We investigated nine human fetuses with trisomy 13 and gestational ages of 14-19 weeks. Whole body radiographs and radiographs of midsagittal tissue blocks of the cranial base and the spine were studied. In the youngest fetus, 14 w GA, no malformations were observed. In eight fetuses, 17-19 weeks GA, malformations occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This study demonstrates that in prenatal triploidy cases not only malformed vertebral corpora occurred but also abnormal cartilaginous tissue (2–7, 11). This is what could be expected, as the adequate synthesis of glycosaminoglycans is a prerequisite for normal embryogenesis including bone development (10).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study demonstrates that in prenatal triploidy cases not only malformed vertebral corpora occurred but also abnormal cartilaginous tissue (2–7, 11). This is what could be expected, as the adequate synthesis of glycosaminoglycans is a prerequisite for normal embryogenesis including bone development (10).…”
Section: Discussionmentioning
confidence: 76%
“…Earlier radiographic studies of prenatal cases with known genotypes including triploidy have demonstrated phenotypic malformations in the axial skeleton compared to normal development (2–8). Also skeletons from prenatal cases with well known phenotype but unknown genotype have been described (6, 7).…”
mentioning
confidence: 99%
“…However, it was not possible to classify the cranial base malformations according to a specific pattern of column malformations, in part due to small numbers in the present study. The axial segmental differences in expression of HOX genes may explain why some spine segments are malformed, while others are not [Kjær et al, 1996, 1997a; Keeling et al, 1997; Nolting et al, 2000].…”
Section: Discussionmentioning
confidence: 99%